Ultrasound-assisted extraction of polyphenols from Chinese propolis - Peng, Shiqin; Zhu, Meifei; Li, Shanshan; Ma, Xiaobin; Hu, Fuliang (Frontiers in Sustainable Food Systems, 2023)
Introduction Propolis is a beneficial bioactive food with rich polyphenols content. Nowadays, an increasing interest is attracted to the extraction of polyphenols from raw propolis. This study utilized the novel ultrasound-assisted approach for polyphenol extraction from Chinese propolis, aiming to improve its extraction yield and reveal the relevant mechanisms via extraction kinetic study as well as the compositional and structural analysis. Methods The optimum ultrasound-assisted extraction conditions were optimized according to the total phenolic content and total flavonoids content. Compositional and structural analysis were conducted using high performance liquid chromatography-quadrupole-time of flight tandem mass spectrometry, high-performance liquid chromatography, Fourier-transform infrared spectroscopy (FT-IR) and scanning electron microscope (SEM). Results and discussion The optimum ultrasound-assisted extraction conditions were as follows: ratio of liquid to solid, 60:1; ultrasound power, 135 W; ultrasound duration, 20 min. Under the optimum conditions, the antioxidant activities of the extract were increased by 95.55% and 64.46% by 2,2-diphenyl-1-picrylhydrazyl radical scavenging ability assay and 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging ability assay, respectively, compared to those obtained by traditional maceration. The second-order kinetics model was employed to study the extraction process; it was found that ultrasound significantly accelerated the extraction of propolis and increased the maximum extraction volume of phenolic compounds. The qualitative and quantitative analysis of polyphenol compositions showed that ultrasound did not change the polyphenol types in the extract but it significantly improved the contents of various flavonoids and phenolic acids such as galangin, chrysin, pinocembrin, pinobanksin and isoferulic acid. Likewise, the FT-IR analysis indicated that the types of functional groups were similar in the two extracts. The SEM analysis revealed that the ultrasound-assisted extraction enhanced the contact areas between propolis and ethanol by breaking down the propolis particles and eroding the propolis surface.